(untitled) (Myśl Ekonomiczna i Polityczna, 2013)
Further economic and monetary integration in Europe is currently on hold due to the economic crisis and even questions about a possible Greece exile. Especially in those conditions it is important to see whether integrated Europe can handle future problems and if economic and monetary integration can be helpful or rather more problematic. The main aim of this paper is to check to what degree business cycles are synchronized in the Eurozone and the European Union and what the main determinants of business cycles synchronization are. To achieve it, the following steps are taken. Firstly, we turn to optimum currency area theory to see what conditions need to be met if the European Union and the Euro Area can use common monetary policy to deal with some economic shocks. Then all necessary methodological explanations are put. Later on, the preliminary data analysis is employed to see how business cycles and their determinants have been acting during the last 20 years. Finally, panel data analysis is used to check how those determinants actually influence business cycles synchronization. The main finding of the article is that even though business cycles synchronization has been progressing in the European Union and the Euro Area, so has the specialization – divergence in production structure. This may result in less synchronized business cycles in the future.